KORELASI KEBIASAAN MEMBACA TERHADAP KEMAMPUAN MEMBACA PEMAHAMAN PADA SISWA KELAS VII SMP NEGERI 1 MAMBI - Kurnia Kurnia; Nur Hafsah Yunus; Handayani Handayani (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2022)
This study aims to determine the relationship between reading habits and the ability to read grade VII students of SMP N 1 Mambi. The analytical method used in this study is a quantitative research method with a correlational design. The population in this study were all students of SMP N 1 Mambi, the sample of this study was class VII students with a total of 57 students. The instruments used are test sheets and questionnaires. Data collection techniques in this study are test and non-test techniques—data analysis techniques, namely descriptive statistics and inferential statistics parametric inferential Pearson correlation. The descriptive statistical analysis of reading habits results showed that the highest score was 92.50 and the lowest score was 54.17. Then the total number obtained is 4254.13, and the average is 74.6339. The results of descriptive statistical analysis of reading comprehension ability showed the highest score obtained was 89.29 and the lowest score was 25.00. Then the total number obtained is 3510.68, and the average is 61.5909. shows that when the Pearson Correlation is -0.120 and sig. (2-tailed) is 0.347. Because of sig. (2-tailed) is higher than (0.05) then it can be stated that there is no relationship between reading habits and reading comprehension.